Bullying Sebagai Penghambat Kedewasaan Remaja di Bekasi - Chantika Nurul Wijayanti; Cindy Tiara Adinda; Hanna Aqeela Humayra; Mochammad Aqshal Sallim; Syafira Suniyah Nur Fahmi; Mic Finanto Ario Bangun (Universitas Maritim AMNI Semarang, 2024)
The study examines the impact of bullying on adolescent maturity in Bekasi, using methods of literary study. Factors such as the psychological condition of the perpetrators and victims, the family environment, and the school culture play a role in the occurrence of bullying. Bullying can lead to mental health disorders and decreased academic performance in adolescents, which in their behavior can hinder their progress towards maturity. The study analyzed patterns of relationships between bullying experiences and aspects of adolescent maturity, such as emotions, cognition, and behavior. Factors that moderate the negative impact of bullying are also being explored.